Clinical profile of organophosphorous poisoning in children admitted to tertiary care hospital - Wani, Jawad Nazir; Pandita, Vivek; Yousuf, Saleem; Giri, Farhat (International Journal of Contemporary Pediatrics, 2020)
Background: Organosphophorous compounds are the commonly available insecticides in households. Therefore, children are vulnerable to accidental poisoning. It is associated with significant morbidity and mortality. The aim of this study was to study the clinical profile of organophosphorous poisoning in children. Methods: This was prospective study conducted over a period of two years from January 2018 to January 2020 in department of Pediatrics, Government Medical College Srinagar, Jammu and Kashmir, India. All the patients in the age group of 1-18 years with history and examination suggestive of organophosphorous poisoning were included in this study. Results: In this study there were total of 54 patients. In majority of cases poisoning was accidental. Oral consumption was most common route of poisoning. The most common symptoms were excessive salivation (100%), vomiting (72%), abdominal pain (26%), diarrohea (13%), agitation (11%) and convulsions (3.7%). The most common signs were miosis (78%), bradycardia (59%), fasciculation (57%) and altered sensorium (13%). Respiratory failure and circulatory collapse were two main complications which contributed to mortality in this study. Conclusions: Organophosphorous poisoning is one of the most common poisoning in children. Early diagnosis and treatment is of pivotal importance to prevent mortality.